Molecular Biology, Pharmacology and Functional Role of the Plasma Membrane Dopamine Transporter - Sotnikova, Tatyana D.; Beaulieu, Jean-Martin; Gainetdinov, Raul R.; Caron, Marc G. (CNS & Neurological Disorders - Drug Targets, 2006)
The plasma membrane dopamine transporter (DAT) tightly regulates the extracellular concentrations of dopamine (DA) by re-capturing released neurotransmitter back into the presynaptic neuronal terminals and/or neighboring DA projections thereby providing an effective way to regulate synaptic and extrasynaptic DA levels. This transporter is a primary target of many potent psychotropic drugs and neurotoxins, such as cocaine, amphetamines and 1-methyl-4- phenyl-1,2,3,6-tetrahydropyridine (MPTP). In this review we summarize recent advances in understanding the structure, regulation, and functional roles of DAT in normal DA physiology and pathological conditions, such as attention deficit hyperactivity disorder (ADHD) and neurodegenerative processes, as well as their contribution to the pharmacology of psychostimulant drugs. Significant new insights on these issues have been gained using mice with genetic deletion of DAT.
Keywords: serotonin